Assessment of Educational Needs and Design of a Preceptor Development Program for Health Professional Education Programs in Qatar. Issue 1 (24th June 2022) - Mukhalalati, Banan; Awaisu, Ahmed; Elshami, Sara; Paravattil, Bridget; Zolezzi, Monica; Abu-Hijleh, Marwan; Moslih-Almoslih, Ayad; Carr, Alison; Bawadi, Hiba; Romanowski, Michael; Almahasneh, Randa; Bacha, Rasha
Abstract : Introduction: Experiential learning is the backbone of many health care professional education programs; however, the quality of learning is profoundly dependent on the skills and experiences of clinical preceptors. This study was conducted at Qatar University Health Cluster (Colleges of Pharmacy, Medicine, and Health Sciences) with the primary objective of identifying the educational needs of preceptors to design and review an educational professional development program. Methods: This study adopted a mixed-methods approach and was conducted in three stages: (1) assessment of preceptor educational needs, (2) designing of the Practice Educators' Academy program, and (3) revision and refinement of the designed program. The needs' assessment was conducted at all the three colleges through a validated survey and focus groups comprising of preceptors, students, and clinical faculty members. The sample included 209 survey respondents and 11 focus group sessions. Results: The results yielded five key themes and a variety of individual preferences, which were used to design a five-module face-to-face two-day interactive workshop. For the revision of the designed program, the syllabus was shared purposively with selected scholars and experts in the area of health professions education, and their feedback was collected and critically examined. Furthermore, the refinement of the program was performed on the basis of this feedback, resulting in the revised and representative program being ready for piloting. Discussion: A preceptor development program on experiential teaching and learning skills was successfully designed and revised with the needs of the clinical preceptors at its core. Preceptors' skills development can advance health care outcomes by preparing competent health professional graduates.